2016
DOI: 10.1186/s13000-016-0457-7
|View full text |Cite
|
Sign up to set email alerts
|

TRPV6 plays a new role in predicting survival of patients with esophageal squamous cell carcinoma

Abstract: BackgroundTRPV6 is over-expressed and promotes the proliferation and invasion in many cancers. The association between the expression of TRPV6 and clinical outcome in esophageal squamous cell carcinoma (ESCC) has not been studied yet. We aim to elucidate the role of TRPV6 in predicting prognosis of patients with ESCC.MethodsIn the retrospective study, mRNA level of TRPV6 was examined in patients (N = 174) from Sun Yat-sen University Cancer Center (mRNA cohort) and protein level of TRPV6 was examined in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The TRPV6 channel is a calcium cation channel protein, which is the major constituent of superfamily of transient receptor potential (TRP) channels, further in terms of subfamily vanilloid member 6, which regulates the calcium homeostasis in the epithelial tissue of human organs (3). TRPV6 is overexpressed in colon cancer, breast cancer, prostate cancer, parathyroid cancer and thyroid cancer (3)(4)(5)(6), however decreased TRPV6 expression was observed in esophageal cancer, non-small cell lung cancer and renal cancer (7)(8)(9). Overexpression of TPPV6 in many cancers indicates the idea of this protein as encoded by a probable oncogene, but the level of TRPV6 in other cancers showed a tendency of a tumor-suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…The TRPV6 channel is a calcium cation channel protein, which is the major constituent of superfamily of transient receptor potential (TRP) channels, further in terms of subfamily vanilloid member 6, which regulates the calcium homeostasis in the epithelial tissue of human organs (3). TRPV6 is overexpressed in colon cancer, breast cancer, prostate cancer, parathyroid cancer and thyroid cancer (3)(4)(5)(6), however decreased TRPV6 expression was observed in esophageal cancer, non-small cell lung cancer and renal cancer (7)(8)(9). Overexpression of TPPV6 in many cancers indicates the idea of this protein as encoded by a probable oncogene, but the level of TRPV6 in other cancers showed a tendency of a tumor-suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…internal anaerobic metabolism of cancer cells is highly activated (34), therefore, LDH acts as a biomarker for tumor burden, and reflects tumor progression and tumor burden (35). In resent, several studies on cancer related elevation of LDH have been reported, and prognostic significance of serum LDH has been verified (21,31,(35)(36)(37)(38). Similarly, in this study on the prognostic role of LDH in TC, we found that the elevated pretreatment serum LDH level was associated with poor OS and short DFS after resection of TC.…”
Section: Discussionmentioning
confidence: 96%
“…LDH is abundant in some organs, such as heart, liver, kidney and muscle. When these organs are affected by malignancies, inflammation and toxicity, LDH releases from the cracked cell, which finally results in the elevation of serum LDH level (31,32). Rapid progression of malignancies leads to low-oxygen conditions in tumor microenvironment (33), for adapting to these conditions, CT + S + CRT 1 (1.7)…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer (ESCC) is a kind of malignant tumor of digestive system which occurs in esophageal epithelial tissue [1]. The histopathological types of esophageal cancer can be divided into two types, one is ESCC [2], the other is esophageal adenocarcinoma [3]. China has a high incidence of ESCC [4].…”
Section: Introductionmentioning
confidence: 99%